Ionospheric Seismology: Some societal implications - Reddy, C.D. (My University, 2016)
The Lithosphere, Atmoshpere and Ionosphere (LAI) is a coupled system and continuously exchange energy through various coupling mechanisms. It is well established that seismic events are coupled to the ionosphere though atmosphere. Earthquakes induce detectable ionospheric plasma perturbations, carrying traceable information about the earthquake that generated them. Inferring the seismological information from these seismo-ionospheric manifestations is the subject that pertains to ionospheric seismology. In this manuscript, after introducing ionospheric seismology, two important societal implications are discussed. (1) From the ionosheric plasma response to 2015 Nepal earthquake, Rayleigh group velocity has been estimated for Indian region and validated from ground measurements. This is considered as one of the most potential applications of the ionspheric seismology. (2) Tsunamis are caused by earthquakes or volcanic eruptions under the sea. Tsunami warning has been discussed based on the GNSS data and assumes importance as it is going to be promising tool in augmenting the existing tsunami warning systems.
Keywords: Acoustic waves; GPS; Earthquake; Ionosphere; Plasma; Seismology; TEC